The Correlates of Household Income, Family Size, and Occupation and Increase of Wood Fuel Consumption - Tagupa, Cristopher (JPAIR Multidisciplinary Research, 2017)
As more people consumed and burned wood fuels, in addition to fossil fuel combustion, carbon dioxide concentrations continue to rise, resulting to further increase in the global temperature. The study estimates the amount of carbon dioxide emissions from wood fuel consumption in the three municipalities. There were 450 respondents randomly interviewed using structured questionnaire. Findings revealed that firewood is the main type of fuel energy used by the households for cooking. Cocos nucifera, Acacia mangium, Sweitenia macrophylla, gmelina arborea, Gliricidia cepium, Hevea brasilliensis, Melia dubia and Leucaena leucocephala, Elaeis quineensis, Crysophyllum caimito, and Sandoricum koetjape are among the known species used as firewood and charcoal, mainly collected from their own farms. The daily consumption of wood fuel for every household ranges from 2.81 kg - 4.48 kg (about 2,484.26 kg to 8,822.22 kg annually). Carbon dioxide emissions from wood fuel is estimated to 18,247.04 kg/year. Further, regression analysis showed that CO2 emissions from wood fuel can be determined through the following equations: CO2 Emissionsfirewood= -3.86-10 + 1.65*weight of firewood; CO2 Emissionscharcoal= 4.814-7 + 3.667*weight of charcoal. Household’s income, family size and occupation are associated with a little increase of wood fuel consumption.